2013
DOI: 10.3892/ol.2013.1770
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 37 human papillomavirus types in parotid gland tumor tissues

Abstract: Human papillomavirus (HPV) infection has been shown to be associated with human tumorigenesis. The aim of the present study was to demonstrate the association between HPV infection and parotid gland tumors. Paraffin-embedded tissue sections from 59 cases of parotid gland tumors and 20 normal oral mucosa were subjected to DNA extraction and flow-through hybridization and gene chip technology to detect infection of 37 HPV types. The HPV-positive rate was 57.6% in parotid gland tumor paraffin-embedded tissue spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…This method, called HybriMax, can be used to simultaneously identify 21 different HPV genotypes, including 14, 5, and 2 genotypes of HR‐HPVs, LR‐HPVs and unknown‐risk HPVs, respectively. This identification is particularly useful for detecting multiple or coinfections of different HPV genotypes, and HybriMax is a reasonable or even ideal technique for performing HPV genotyping in a clinical setting …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method, called HybriMax, can be used to simultaneously identify 21 different HPV genotypes, including 14, 5, and 2 genotypes of HR‐HPVs, LR‐HPVs and unknown‐risk HPVs, respectively. This identification is particularly useful for detecting multiple or coinfections of different HPV genotypes, and HybriMax is a reasonable or even ideal technique for performing HPV genotyping in a clinical setting …”
Section: Discussionmentioning
confidence: 99%
“…All the DNA samples were amplified using the Real‐Time PCR system ABI 7500 (Applied Biosystems, USA) using a PCR reagent kit (Chaozhou Hybribio Biochemical Co., Ltd.). HPV genotyping was performed with a HybriMax HPV GenoArray Test Kit (HybriBio Ltd., Chaozhou, China) according to the manufacturer’s instructions . Positive and negative controls were run in each PCR analysis process to control for possible contamination and accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…showed that HPV DNA was absent in Warthin's tumour, a benign salivary epithelial neoplasm. In contrast, Teng et al . detected the presence of HR‐HPVs, including HPV16 and HPV18, in four of 12 (33%) Warthin's tumours.…”
Section: Discussionmentioning
confidence: 85%
“…detected the presence of HR‐HPVs, including HPV16 and HPV18, in four of 12 (33%) Warthin's tumours. Similarly, the reported incidence of HR‐HPV in mucoepidermoid carcinoma, the most common malignant salivary gland epithelial tumour, varied from 0% to 47–100% . With regard to ParSCC, the only case with a documented HPV status was reported by Fischer and Von Winterfeld, who detected the presence of HPV in a single case of ParSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation